Immune reconstitution inflammatory syndrome and the influence of T regulatory cells: a cohort study in The Gambia. - Zaidi, I; Peterson, K; Jeffries, D; Whittle, H; de Silva, T; Rowland-Jones, S; Jaye, A; de Jong, B (Public Library of Science, 2012)
The factors associated with the development of immune reconstitution inflammatory syndrome in HIV patients commencing antiretroviral therapy have not been fully elucidated. Using a longitudinal study design, this study addressed whether alteration in the levels of T regulatory cells contributed to the development of IRIS in a West African cohort of HIV-1 and HIV-2 patients. Seventy-one HIV infected patients were prospectively recruited to the study and followed up for six months. The patients were categorized as IRIS or non-IRIS cases following published clinical guidelines. The levels of T regulatory cells were measured using flow cytometry at baseline and all follow-up visits. Baseline cytokine levels of IL-2, IL-6, IFN-(Gamma), TNF-(Alpha), MIP-1(Beta), IL-1, IL-12, IL-13, and IL-10 were measured in all patients.